The development of a method for assessing the preparation of aviation personnel participated in ensuresing flight safety - Dolzhenko, Nadezhda (Eastern-European Journal of Enterprise Technologies, 2023)
The problem solved in the research is to increase the efficiency of decision making in the tasks of professional training of pilots while ensuring the specified reliability, regardless of the hierarchy of the system of evaluation indicators. The object of the research is the professional training system for civil aviation pilots. The subject of the research is the process of assessing the qualities of civil aviation pilots using fuzzy cognitive maps. The hypothesis of the research is to increase the number of indicators for assessing the quality of training of civil aviation pilots with restrictions on the efficiency and reliability of decision making. A method has been developed for assessing the preparedness of aviation personnel involved in ensuring flight safety. The method consists of the following sequence of actions: – input of initial data; – standardization of numerical values of concepts of a fuzzy cognitive model of preparedness of aviation personnel involved in ensuring flight safety; – transition of numerical values of concepts of a fuzzy cognitive model of preparedness of aviation personnel involved in ensuring flight safety; – building a fuzzy cognitive model; – determination of quantitative estimates (ranks) of the importance of model elements; – calculation of importance indices of model elements. Based on the results of the analysis of the effectiveness of the proposed method, it is clear that the proposed assessment method increases the accuracy of the assessment of aviation personnel involved in ensuring flight safety by 23 % compared to the known ones. It is advisable to use the developed method in decision making support systems for assessing the quality of professional training of aviation personnel in order to increase the efficiency and reliability of decisions made.